STRATEGI PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDesa) DI DESA MATTIRO ADE KECAMATAN PATAMPANUA KABUPATEN PINRANG - Ramli, Sulastriyani; Parawangi, Anwar; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2023)
The purpose of the study was to find out the strategy for developing Village Owned Enterprises (BUMDesa) in Mattiro Ade Village, Patampanua District, Pinrang Regency. This study used descriptive qualitative and phenomenological approach with a total of four informants. The results showed that the organizational strategy seen from its relationship with the program being implemented had met the indicator criteria of the organizational strategy. The strategy for supporting resources had not been fully achieved, although the facilities and infrastructure, human resources, and financial resources had run well, but the utilization of natural resources had not been implemented. The program strategy had been fulfilled through a hydroponic lettuce cultivation program which had implications for the community and organizations from the profits obtained. The institutional strategy was also going well, seen from the communication and coordination between the management and the evaluation to see the progress of the performance of the Sipakalebbi BUMDesa management.